Missing the Impact in Impact Investing Research – A Systematic Review and Critical Reflection of the Literature - Deike Schlütter; Lena Schätzlein; Rüdiger Hahn; Carolin Waldner (Journal of Management Studies, 2023)
Impact investing (II) aims to achieve intentional social impact in addition to financial return. Our systematic literature review of 104 articles finds that the growing academic literature on II is scattered across a variety of disciplines and topics, with inconsistencies in terminology and concepts and a paucity of theoretical explanations and frameworks. To provide an overview of common research areas and findings, we integrate the articles on II in nine emerging topics and shed light on inconsistencies in the literature. The analysis reveals one major shortcoming in II research: Despite the fact that II aims to create a measurable societal impact, this impact of II, its raison d'être, is not scrutinized in the literature. We argue that investigating the impact of II requires a holistic lens, for which we propose systems theory. We suggest prospective future research avenues which combine socio-economic research approaches (esp. longitudinal qualitative studies and experimental methods) with socio-technical methods (esp. life cycle analysis) to enable a holistic systems perspective of II.
Keywords: 650; impact investing; literature review; research methods; social finance; sustainable finance; systems theory